2004
DOI: 10.1016/j.neuron.2004.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Striatal Dopamine Signaling by Amphetamine Inhibits Feeding by Hungry Mice

Abstract: and A substantial literature is consistent with the hypothesis that systemic AMPH reduces appetite by release of Howard Hughes Medical Institute University of Washington catecholamines within the perifornical lateral hypothalamus (pfLH) (Baptista et al., 1993; Chen et al., 2001; Kuo,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 119 publications
1
49
0
Order By: Relevance
“…The mice were allowed to acclimate for 3 days before initiating DT treatment and data collection. Body weight and intake of liquid diet were recorded every 24 h. Licking activity at food and water dispensers was monitored continuously by computer as described (24,49). Licking data were processed and grouped into 2-h bins by using the MatLab software (Mathworks).…”
Section: Methodsmentioning
confidence: 99%
“…The mice were allowed to acclimate for 3 days before initiating DT treatment and data collection. Body weight and intake of liquid diet were recorded every 24 h. Licking activity at food and water dispensers was monitored continuously by computer as described (24,49). Licking data were processed and grouped into 2-h bins by using the MatLab software (Mathworks).…”
Section: Methodsmentioning
confidence: 99%
“…Other important anorexigenic factors include serotonin (via 5HT 1b , 5HT 2A , and 5HT 2C receptors) and corticotropin-releasing hormone (CRH; Kalra et al, 1999;Makarenko et al, 2002;Muller et al, 2004), whereas orexigenic processes are favored by endogenous opiate peptides (Morley, 1987; Horvath et al, (Kalra et al, 1999). Lastly, basal ganglia dopamine is involved in nonhedonic metabolic drive and goal-directed motor behavior towards procurement of food (Volkow et al, 2002c;Cannon et al, 2004).…”
Section: Neurobiology Of Systems Mediating Caloric Balancementioning
confidence: 99%
“…Other important anorexigenic factors include serotonin (via 5HT 1b , 5HT 2A , and 5HT 2C receptors) and corticotropin-releasing hormone (CRH; Kalra et al, 1999;Makarenko et al, 2002;Muller et al, 2004), whereas orexigenic processes are favored by endogenous opiate peptides (Morley, 1987; Horvath et al, (Kalra et al, 1999). Lastly, basal ganglia dopamine is involved in nonhedonic metabolic drive and goal-directed motor behavior towards procurement of food (Volkow et al, 2002c;Cannon et al, 2004).As a whole, this well-orchestrated machinery is almost infallible in preventing caloric deficit states as it sets of hunger (and supresses satiety), accompanied by negative subjective experiences ranging from slight discomfort to restlessness and food obsession. Eating can therefore be construed as a negative reinforcer as it brings an end to the discomfort induced by hunger (Saper et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The dopamine neurotransmitter functions in reward-motivated behaviors; thus, changes to extracellular dopamine levels can result in a number of diseases (Palmiter, 2007;Yamamoto and Seto, 2014). Low levels of dopamine are associated with attention deficit hyperactivity disorder (ADHD), depression, and under-eating (Cannon et al, 2004;Sotak et al, 2005). Studies in rats showed that upon feeding or drinking, there was a rapid firing of dopamine in the brain.…”
Section: Introductionmentioning
confidence: 99%